2013
DOI: 10.4172/2329-8901.1000110
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic Activity of Bacillus Bacteria against Food-Borne Pathogens

Abstract: Bacillus bacteria have attracted the attention of scientists as promising probiotics because of their versatile antimicrobial activity and established health benefits on the host. In this study, seven Bacillus strains were identified and analyzed for antagonistic activity against broad spectrum of food borne pathogens. All strains were identified as B. subtilis, based on the results of morphological, biochemical characterization and 16S rDNA sequence analysis. B. subtilis strains demonstrated antagonistic acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 34 publications
3
16
0
2
Order By: Relevance
“…It can be observed in the images included in Figure 6 that in TSA media, the growth of the strain isolated from CSW was not affected by the pathogenic strains used in the experiment. Therefore, it correlates with previous works where Bacillus bacteria shown to have inhibitory abilities against food-borne pathogens (Moore, Globa, Barbaree, Vodyanoy, & Sorokulova, 2013), probably due to the production of secondary metabolites such as the biosurfactants like those isolated in the current work. Likewise, in SDA medium, the isolated Bacillus strain was able to grow in the presence of C.albicans and S.aureus though it was not the case of A.niger, where the pathogen covered the isolated Bacillus strain.…”
Section: Antagonist Effect Of the Microorganism Isolated From Csw On supporting
confidence: 91%
“…It can be observed in the images included in Figure 6 that in TSA media, the growth of the strain isolated from CSW was not affected by the pathogenic strains used in the experiment. Therefore, it correlates with previous works where Bacillus bacteria shown to have inhibitory abilities against food-borne pathogens (Moore, Globa, Barbaree, Vodyanoy, & Sorokulova, 2013), probably due to the production of secondary metabolites such as the biosurfactants like those isolated in the current work. Likewise, in SDA medium, the isolated Bacillus strain was able to grow in the presence of C.albicans and S.aureus though it was not the case of A.niger, where the pathogen covered the isolated Bacillus strain.…”
Section: Antagonist Effect Of the Microorganism Isolated From Csw On supporting
confidence: 91%
“…While the main interest in the beneficial endophytic Bacillus is on controlling plant diseases (Bacon and Hinton, 2002;Liu et al, 2009) and/or promoting plant growth (Bai et al, 2002;Rajendran et al, 2008), some endophytic Bacillus strains have been found to be inhibitory against human pathogens, including Bacillus cereus, Clostridium perfringens, E. coli, L. monocytogenes, S. enterica Typhymurium, and Shigella flexineri (Bacon and Hinton, 2002;Földes et al, 2000;Islam et al, 2010;La Ragione et al, 2001;La Ragione and Woodward, 2003;Moore et al, 2013;Pinchuk et al, 2002;Sabaté and Audisio, 2013). However, there is little information on the use of anti-human-pathogen endophytic Bacillus strains as biocontrol agents to reduce the food safety risk of fresh produce.…”
Section: Discussionmentioning
confidence: 99%
“…Production of an antimicrobial substance from B. subtilis can be affected by growth conditions, such as medium composition, growth temperature, and bacterial physiological state. Moore et al (2013) reported that seven wild B. subtilis strains displayed inhibitory activity against pathogens only on starch agar at 30 o C, but not at 37 o C or on trypticase soy agar (TSA) or nutrient agar at either 30 o C or 37 o C. In other studies, B. subtilis 168 was found to produce bacilysocin on TSA immediately before or early in sporulation, respectively (Stöver and Driks, 1999;Tamehiro et al, 2002). In our preliminary tests, it was noticed that the inhibition zones of the B. subtilis isolates against the S. enterica or E. coli indicator on LB agar plates were generally smaller than those on DSM agar plates.…”
Section: Discussionmentioning
confidence: 99%
“…telah diketahui sebagai bakteri-bakteri yang mampu menghasilkan senyawa antibiosis yang beragam. Tidak terbentuknya zona hambatan yang dikarenakan kondisi media tumbuh yang digunakan juga telah dilaporkan oleh Moore et al (2013), dimana pada penelitian tersebut tujuh strain Bacillus yang digunakan tidak memperlihatkan adanya zona hambatan terhadap enam bakteri patogen pada tiga jenis media (NZY agar, NA (Nutrient Agar) dan TSA (Trypticase Soy Agar) dari empat jenis media yang digunakan. Al-Zahrani (2007) menjelaskan bahwa senyawa antibiosis sangat dipengaruhi oleh komposisi medium, baik secara kuantitatif maupun kualitatif.…”
Section: Pembahasanunclassified